Vis-à-Vision conversations with Russian artists 1979-2013 - Agamov-Tupicyn, Viktor 1945- (Spector Books, 2017)
In the Soviet era, poet, critic and cultural theorist Victor Tupitsyn had already begun making recordings of his conversations with Russian conceptualist artists in their Moscow kitchens and studios. These recordings were intended for readers who had no access to this group of artists, whose work ran afoul of the official Soviet conceptions of art and thus was not shown in exhibitions. Like many other Russian intellectuals and artists, Tupitsyn emigrated to New York in the 1970s, where he continued the conversations he had begun. Victor Tupitsyn: Vis-à-vision collects Tupitsyn's conversations in full for the first time, featuring interviews with Ilya Kabakov, Boris Mikhailov, Komar&Melamid, Erik Bulatov and the groups Collective Actions and Inspection Medical Hermeneutics as well as many others. This body of interviews is an invaluable historical document of one of the most influential art tendencies of the late 20th century.